Measurement invariance across mother/child and father/child attachment relationships - Fernandes, M. (2020)
We examine the factorial structure of the Security Scale Questionnaire (SSQ), exploring measurement invariance across mother-father-child attachment relationships, child sex, and country. We used the new 21-item SSQ version that integrates both safe haven and secure base behaviors in a two factors structure. Participants were 457 children (224 girls and 233 boys), ranging from 9 to 14 years old (M = 10.84, SD = 1.02) from Portuguese and USA samples. We confirmed the SSQ's two-factor structure, although four items were unrelated to the latent structure and excluded from the final model. Results showed that SSQ can be used to study both mother/child and father/child attachment relationships. Multi-group analyses suggested measurement invariance between boys and girls and between Portuguese and USA samples. Our findings suggest that the SSQ can be considered a valid and cost-effective tool to measure perceived attachment security in middle childhood for both mother/child and father/child relationships.